Leverage Keuangan Dan Kompensasi Manajemen: Studi Empiris Pada Industri Konsumsi Siklis - Farihah, Elva; Hartadinata, Okta Sindhu; Wahyu Bintang Maulana, Afandi Ukik (Unversitas Islam Madura, 2024)
This study investigates the effect of financial leverage on managerial compensation. The sample used was 24 companies from consumer cyclical industry on 2018-2022 so that the total observation was 120 firm-year. This study shows that financial leverage has negative effect on managerial compensation. It provides implication that the effect of financial leverage on managerial compensation is relevant to agency theory. Both of them have same function to minimize agency problem then can substitute each other. The firm can consider this finding in determining the optimal scheme of compensation.